Pd(II)-catalyzed chemoselective acetoxylation of C(sp(2))-H and C(sp(3))-H bonds in tertiary amides - Vijaykumar, Muniyappa; Punji, Benudhar (Journal of Organic Chemistry, 2021)
Palladium-catalyzed chemoselective C(sp(2))-H and C(sp(3))-H acetoxylation of synthetically useful tertiary amides is reported under relatively mild reaction conditions. This protocol proceeds through the assistance of a weakly coordinated directing group (C = O) and requires low catalyst (1.0 mol %) loading. Diverse functionalities, such as C(sp(2))-Cl, C(sp(3))-Cl, -CF3, -COOEt, and -NO2 groups, including morpholinyl, piperazinyl, and pyrrolidinyl heterocycles, are compatible under the reaction conditions. Further functionalization of this protocol is demonstrated by hydrolysis to alcohols, alcohol-acids, as well as reduction to tertiary amines. A preliminary kinetic isotope effect study supported the rate-limiting C-H bond activation process.